Bionomic of Anopheles sp. in Merauke District, Papua - Rahardjo, Djoko; Prakasita, Vinsa Cantya; Pepiana, Marlen Aviati Sarah (Universitas Kristen Duta Wacana, 2020)
Malaria is known as an endemic disease that often causes death in Indonesia, especially in Papua. The malaria cases control in Papua has not been carried on based on data studies, therefore bionomic of Anopheles sp is important to be studied. Bionomics data are consisted of breeding places, resting places and feeding habits are from direct observation. Interviews and questionnaires were conducted to gain information about respondent behavior. Descriptive and qualitative data were then analyzed. The breeding places of Anopheles sp. were mostly found in swampy areas. Based on the feeding habit, the feeding activity of Anopheles sp. inside the house has only one biting peak at 23.00-02.00 WIT, while outside the house, biting peaks occurred at 21.00-22.00 WIT and 00.00-01.00 WIT. Resting place data shown that Anopheles sp. mostly found in piles of clothes and shoe racks. Recorded factors that affect mosquitos bionomics are temperature, humidity, salinity, pH, community behavior, and the presence of livestock. Environmental factors (temperature, humidity, salinity, and pH), habitual behavior of host (3M action, the habit of using insect repellent, mosquito repellent, and mosquito nets), the presence of livestock, and the type of bait blood type affect mosquito activity